Deskripsi Tingkat Kecemasan Karir Pada Mahasiswa Institut Attanwir Bojonegoro - Naili Filhayati; Indah Fajrotuz Zahro (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to determine the description of the level of career anxiety in students of the Attanwir Institute of Bojonegoro. The population is 60 students with random sampling techniques in the study. The research method is descriptive quantitative. The career anxiety scale is a Likert scale of 50 statements divided into favorable and unfavorable items with alternative answers strongly agree, agree, disagree and strongly disagree which are compiled from the concept of Tsai, Hsu & hsu, namely aspects of personal skills, irrational beliefs about work, work environment, education and professional training. Researchers use a used tryout scale. Validity test with product moment technique and reliability test using alpha cronbach technique with SPSS 26.00 application. From the validity test, 30 valid items were obtained while the results of the reliability test were 0.935 including very strong reliability. The range of career anxiety levels of students at the Attanwir Institute of Bojonegoro is a high group of 11 students, a medium group of 43 students, and a low group of 6 students. The results of this study provide an explanation to students to prevent career anxiety in final year students so that they can manage career anxiety so that it is not excessive.